Production of lipopeptides among Bacillus strains showing growth inhibition of phytopathogenic fungi - Velho, R. V; Medina, L. F. C; Segalin, J; Brandelli, A (Folia microbiologica, 2011)
The biological activity and the presence of genes sfp and ituD (surfactin and iturin A) among Bacillus strains isolated from the Amazon basin were determined. Bacillus spp. were tested for hemolytic activity and inhibition of fungal growth by agar plate assays in parallel with PCR for identification of sfp and ituD genes. All strains tested produced surface-active compounds, giving evidence by lysis of erythrocytes and emulsifying activity on mineral oil and soybean oil. These strains of Bacillus caused growth inhibition of several phytopathogenic fungi, including Fusarium spp., Aspergillus spp., and Bipolaris sorokiniana. The presence of genes ituD and sfp was confirmed by PCR and sequence analysis. The only exception was Bacillus sp. P34 that lacks sfp gene. Lipopeptides were isolated from culture supernatants and analyzed by mass spectrometry. Characteristic m/z peaks for surfactin and iturin were observed, and some strains also produced fengycin and bacillomycin. The remarkable antifungal activity showed by the strains could be associated with the co-production of three or more lipopeptide antibiotics. Screening for novel bacteria producing useful biosurfactants or biocontrol agents for agriculture is a topic of greatest importance to eliminate chemical pollutants.
Keywords: antifungální látky; Lipopeptides; Bacillus; Fungi; Surface-Active Agents; povrchově aktivní látky; Antifungal Agents; houby; ACP-S-malonyltransferasa; Acyl-Carrier Protein S-Malonyltransferase; lipopeptidy; rostliny; Bacterial Proteins; Plants; bakteriální proteiny